The role of men's physical attractiveness in women's perceptions of sexual risk: Danger or allure?. (September 2013) - Lennon, Carter A; Kenny, David A
The rate of casual sexual encounters is increasing on college campuses. To decrease sexual risk behavior, information used to judge sexual risk in others needs to be identified. Women rated male targets on willingness to have unprotected sex with the target and likelihood that the target has a sexually transmitted infection. Physical attractiveness was the strongest predictor of ratings, accounting for all the target variance in willingness to have unprotected sex. However, risk factors reported by the target were inconsistent predictors of perceived sexual risk. Findings are discussed within the context of safer sex interventions for college students.